Potential geoeconomic and geopolitical consequences of an expanded BRICS - Alicia García Herrero (EconPol Forum, 2024)
The idea behind the BRICS began as a pure economic concept to acknowledge the growing weight of some major emerging economies. However, when it became a reality, it has evolved into a highly political - and less economic - concept. The BRICS, which has been expanded recently to BRICS+, has become increasingly China-centric with very little interaction among other BRICS members. The recent addition increases the group's heterogeneity, with some members being major oil exporters and others needing external funding. The group seems increasingly focused on the reform of the international monetary system, which now rests on the Bretton Woods Institutions, to give more power to emerging economies. Given the large heterogeneity among the BRICS+ members and China's increasingly central role, how India may react poses another important risk to the group's future.
Keywords: 330